Pengaruh Implementasi Anggaran Berbasis Kinerja terhadap Peningkatan Kinerja Pegawai Badan Usaha Milik Negara: Studi Kasus Pada Perusahaan Listrik Negara (PLN) Ranting Dolok Sanggul - Lubis, Putri Kemala Dewi; Nurfitriana, Aulia; Silaban, Sharma Juliana; Hanum, Sophia; Sriyani, Tinti (As-Syirkah: Islamic Economic & Financial Journal, 2024)
In this research, the implementation of performance-based budgeting has a positive and significant impact on improving the performance of State-Owned Enterprises (BUMN) employees. The research method used is quantitative with a population of 51 employees and a sample of 25 people selected through purposive sampling. The results of the validity test show that all measuring instrument items on the variables of performance-based budget implementation and improving the performance of BUMN employees are valid. Apart from that, the data in this study is normally distributed and there is no heteroscedasticity in the regression model. The results of the regression coefficient test show that the implementation of performance-based budgeting has a positive effect on improving the performance of BUMN employees.